Construção de um cluster HPC para simulações de CFD - Kopp, Ernani Maieski (2012)
The purpose of this monograph is a study on clusters of computers and implements a high-performance cluster using the Windows ® Compute Cluster Server. The research presents theoretical concepts of parallel computing systems, fundamentals of clusters and focusing on core tool features Windows® Compute Cluster Server® to test the applicability of theoretical concepts in the construction of a simple high-performance cluster HPC and its viability for solving specific numerical simulations of CFD programs.